Pengaruh Kompetensi Motivasi dan Reward Terhadap Kinerja Karyawan dengan Semangat Kerja sebagai Variabel Intervening - Syamsul Yahya; Sutrisno Sutrisno; Rita Meiriyanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Human resources are one of the organizational resources that play an important role in achieving its goals. Every organization is managed by humans. Without humans, the organization will not run. Challenges and opportunities in managing and creating organizations often stem from human-related problems. Therefore, in managing human resources (HR), the most vital resource is a strategic central activity. Based on this, this study aims to analyze the effect of competence, motivation, reward on employee performance with morale as an intervening variable. This research was conducted at Sembako Rahap Putra UMKM.The research method is to use a type of quantitative research. The population of this study is 215 employees, the sample in this study is 140 employees. The technique used in collecting data using observation and questionnaires as data collection instruments. Data processing techniques use the SmartPLS 3 application.Based on research at Sembako Rahap Putra MSME, the research results obtained show that competence is less influential in increasing morale with a P-Value of (0.093), Motivation has less effect in increasing Morale with a P-Value of (0.465), Rewards are less influential in increasing morale with a P-Value of (0.172), Morale has a positive effect on Employee Performance with a P-Value of (0.025), Competence has less effect on Employee Performance through Morale with a P-Value of (0.244) , Motivation has little effect on Employee Performance through Morale with a P-Value of (0.238), Reward has less effect on Employee performance through work enthusiasm with a P-Value of (0.431).